THE EFFECT OF SNOWBALL THROWING MODEL IN ABILITY TO WRITING RECOUNT TEXT AT CLASS X OF SMA NEGERI LAWE SUMUR ACADEMIC YEAR 2021/2022 - Afria Devi Yanti; Muhammad Tahir; Meri Vancito (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
Abstract The purpose of this study deals with the effect of snowball throwing model in ability to writing recount text at class X in SMA Negeri Lawe Sumur Academic Year 2021/2022. Its objective is to find out whether the use snowball throwing model has a significance effect in writing recount text. Population and samples used in this study were all students of class X total 36 students. The method used in this study is an experimental method with a one group as pretest and posttest design .This study was carried on using quantitave method. The data was analysed by using t-test. The researcher found the pretest mean = 50,97 , deviation standard = 2,87 and experienced an increase in the posttest mean = 78,47, deviation standart = 3,69. From this analysis, writer found that guided snowball throwing model has significane in teaching writing recount text. It can be proved by the result of the analysis showed that “ ” observed about 35,26 was higher than “ttable” about 2,030 with the level significance is 0,05% it implies that the teacher of English should use snowball throwing model in teaching writing recount text so that the teaching and learning process can be successful